SYMPTOM BENCHMARKS OF IMPROVED QUALITY OF LIFE IN PTSD. Issue 3 (16th February 2016) - Schnurr, Paula P.; Lunney, Carole A.
Abstract : Background: Although research has shown that PTSD symptom change relates to improved quality of life, the question of how much improvement in PTSD symptoms is necessary to result in meaningful improvements in quality of life remains unanswered. We used data from a randomized clinical trial of psychotherapy for PTSD in female military veterans and active duty personnel to examine the correspondence between benchmarks of improvement in PTSD symptoms and changes in quality of life. Methods: Participants were 235 female veterans and Army soldiers who were randomized to 10 weekly sessions of Prolonged Exposure or Present‐Centered Therapy. We operationalized PTSD symptom change in terms of four progressively stringent mutually exclusive definitions—No Response, Response, Loss of Diagnosis, and Remission—successively comparing each category to the prior one: No Response versus Response, Response versus Loss of Diagnosis, and Loss of Diagnosis versus Remission. Outcomes were clinically meaningful improvements and good endpoints in domains of clinician‐rated and self‐reported quality of life. Results: Response was associated with improvement on almost all measures, but with only one good endpoint. Loss of Diagnosis was associated with improvement on all measures except self‐rated social functioning and with achieving a good endpoint on all measures. Remission was associated with improvement in clinician‐rated social impairment and a good endpoint in clinician‐rated occupational impairment. Conclusions: For most domains of quality of life, treating a patient until the patient no longer meets diagnostic criteria would be optimal. For some domains, further improvements may result by helping a patient achieve remission.